Will you boycott?: A study of Malaysian Non-Muslims’ willingness to boycott - Abdul Talib, Asmat Nizam; Abdul Latif, Samshul Amry (2012)
Purpose : This paper examined the motivations and willingness to boycott of Non-Muslim consumers in Malaysia; where Islam is prominent.The underlying base used is an on-going boycott spurred by Palestinian/Israel conflict in the Middle East, which targets American-originated firms operating in Malaysia. Design/Methodology/Approach: Two firms were selected based on their market presence, consumer familiarity and product affordability. In total 340 questionnaires were obtained from Non-Muslim university students and validated by multiple regression analysis. Findings :Three factors were found to be significant in predicting willingness to boycott; which were self-enhancement, perceived egregious behavior, and country image. Originality/value : This paper addressed boycott motivations from the context of Malaysian Non-Muslims quantitatively, based on an issue strongly related to Muslims.The results may have some implications on multinational firms, non- government organizations, policymakers as well the consumers.